Peran UNIFIL dalam Menjaga Stabilitas Kawasan Perbatasan di Wilayah Garis Biru Lebanon-Israel - Nabilaturramadhani Nabilaturramadhani; Imam Fadhil Nugraha (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The United Nations Security Council established the United Nations Interim Force in Lebanon (UNIFIL) at the request of the Lebanese Government due to Israeli aggression in 1978 in accordance to mandate of Resolutions 425 and 426. In the period 2024–2025, UNIFIL’s effectiveness is again in the spotlight as escalation of the conflict increases, including the violation of the 60-day ceasefire by Israel, which has caused new tensions in the border area. This article examines the mechanisms, roles and effectiveness of UNIFIL as an international organization in efforts to realize peace in the Blue Line Region. Using the three realistic approaches to peace with the use of qualitative approach based on the latest articles, journals, and news articles. The study shows that limited geopolitical pressure and inability to directly engage in the conflict have hampered UNIFIL's performance, although its presence continues to play a role in preventing large-scale conflict. So the UNSC emphasizes the fulfillment of the 1701 mandate through communication and negotiation between UNIFIL and Lebanon-Israel for peace on both sides.